Discovery of mmu-lncRNA129814/hsa-lncRNA582795 as a Potential Biomarker and Intervention Target for Ischemia Reperfusion Injury-Induced AKI - Yang L; Xu Y; Pan J; Li R; Lan C; Zhang D (Dove Medical Press, 2024)
Liu Yang,1 Yan Xu,1 Jian Pan,2- 4 Renjie Li,1 Chao Lan,1 Dongshan Zhang2- 4 1Department of Emergency Medicine, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan, People's Republic of China; 2Department of Emergency Medicine, Second Xiangya Hospital, Central South University, Changsha, Hunan, People's Republic of China; 3Emergency Medicine and Difficult Diseases Institute, Second Xiangya Hospital, Central South University, Changsha, Hunan, People's Republic of China; 4Department of Nephrology, Second Xiangya Hospital, Central South University, Changsha, Hunan, People's Republic of ChinaCorrespondence: Chao Lan, Department of Emergency Medicine, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan, 450000, People's Republic of China, Tel +86 13663855629, Email fcclanc@zzu.edu.cn Dongshan Zhang, Department of Emergency Medicine, Second Xiangya Hospital, Central South University, Changsha, Hunan, 410011, People's Republic of China, Tel +86 138 7589 9625, Email dongshanzhang@csu.edu.cnBackground: Acute kidney injury (AKI) is associated with higher perioperative mortality and morbidity, as well as increased medical expenses. The molecular mechanisms underlying ischemia-reperfusion (I/R)-induced AKI remain unclear.Methods and Results: We applied an RT-qPCR assay to measure the expression of mmu-lncRNA129814, hsa-lncRNA582795, and miRNA-494-5p, immunoblotting to detect IL-1α and cleaved caspase-3 expression, and TUNEL staining and flow cytometry (FCM) to evaluate apoptosis. The experiments were conducted using BUMPT and HK-2 cells, as well as C57BL/6J mice. Mechanistically, mmu-lncRNA129814 could sponge miRNA-494-5p and upregulate IL-1α expression to promote cell apoptosis. Furthermore, knockdown of mmu-lncRNA129814 ameliorated I/R-induced progression of AKI by targeting the miRNA-494-5p/IL-1α pathways. Interestingly, hsa-lncRNA582795, a homolog of mmu-lncRNA129814, also promoted I/R-stimulated HK-2 cell apoptosis and AKI progression by regulating the miRNA-494-5p/IL-1α axis. Finally, we found that patients with I/R-induced AKI exhibited significantly elevated plasma and urinary levels of hsa-lncRNA582795 compared to those who underwent ischemia-reperfusion without developing AKI. Spearman's test demonstrated a significant correlation between serum creatinine and plasma hsa-lncRNA582795 in I/R patients. Plasma hsa-lncRNA582795 showed high sensitivity but low specificity (86.7%) compared to urinary hsa-lncRNA582795.Conclusion: The mmu-lncRNA129814/hsa-lncRNA582795/miRNA-494-5p/IL-1α axis was found to modulate the progression of ischemic AKI, and hsa-lncRNA582795 could act as a diagnosis biomarker and potential therapy target of I/R-induced AKI. Keywords: AKI, mmu-lncRNA129814, hsa-lncRNA582795, apoptosis, biomarker